PENGARUH ATRAKSI DAN AMENITAS TERHADAP KEPUASAN WISATAWAN LENGKONG CULINARY NIGHT DI LENGKONG KECIL, KOTA BANDUNG - Subeni, Fajar; Rizkyta, Rida (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2024)
This research explores culinary tourism trends in West Java, Indonesia, with a focus on the popularity of street food at Lengkong Culinary Night in Bandung. Despite gaining popularity, challenges such as limited parking spaces affect visitor accessibility. Using a quantitative method, the study involved 100 visitors with multiple linear regression analysis. Findings indicate a positive impact of attraction and facilities on tourist satisfaction. The research provides insights into factors influencing tourist satisfaction and practical implications for stakeholders in the tourism and culinary sector. Separately, the attraction variable shows a significant impact on tourist satisfaction, as evidenced by the calculated t value of 11.263 which exceeds the t table value of 1.985, with a significance value of 0.000 which is lower than 0.05. Likewise, individual amenity variables also make a significant contribution to tourist satisfaction, as can be seen from the t count of 5.081 which exceeds the t table value of 1.985, with a significance value of 0.000 which is smaller than 0.05. When tested simultaneously, attractions and amenities also show a significant impact on tourist satisfaction, indicated by a calculated F value of 203.147 which exceeds the F table value of 3.09, with a significance value of 0.000 which is smaller than 0.05. Therefore, it can be concluded that both individually and together, attractions (X1) and amenities (X) have a significant influence on the satisfaction variable (Y). Thus, it can be concluded that the hypotheses for the three variables can be accepted.